Comportamento de forrageio e dieta de Calidris pusilla durante diferentes demandas fisiológicas do ciclo migratório - Silva, Leomyr Sângelo Alves da (2021)
Every year thousands of nearctic birds make great migrations between their breeding sites, north of the Tropic of Cancer, to wintering areas in tropical and subtropical regions. Calidris pusilla, one of these birds, frequents mainly South America during its wintering period, using maritime and estuarine regions on the northeast coast of Brazil. In these places, they need the energy necessary to meet the high physiological demands of their migratory cycle, such as changing their plumage and increasing their mass. Thus, Calidris pusilla presents flexibility in foraging mechanisms to prepare against habitat changes, which can cause prey unpredictability. In this study, we tested the hypothesis that: the phases that comprise the migration cycle of Calidris pusilla in South America, present physiological variations in relation to its energy demand, which, consequently, influence foraging strategies. We expect that foraging and diet strategies are associated with the bird's energy demand (change of plumage, flight feather changes and contour), as well as with the availability of prey in the environment. The study was conducted on Ilha da Restinga-PB, a fluvial island located in the Rio Paraíba estuary, Northeastern Brazil. The island has an area of approximately 580 ha, mainly composed of restinga vegetation, lagoons and mangrove areas, which individuals from Calidris pusilla use to forage and exchange their plumage. The results of this research are in accordance with the initially proposed hypothesis. We found that the phases that comprise the migratory cycle of Calidris pusilla present physiological variations in relation to its energy demand, moreover, Calidris pusilla varied the foraging investment to meet its physiological demands, as well as to prevent against prey unpredictability.